Direct optical excitation of a fullerene-incarcerated metal ion - Jones, MAG; Taylor, R; Ardavan, A; Porfyrakis, K; Briggs, G (2006)
The endohedral fullerene Er3N@C80 shows characteristic 1.5 μm photoluminescence at cryogenic temperatures associated with radiative relaxation from the crystal-field split Er3+ 4I13/2 manifold to the 4I15/2 manifold. Previous observations of this luminescence were carried out by photoexcitation of the fullerene cage states leading to relaxation via the ionic states. We present direct non-cage-mediated optical interaction with the erbium ion. We have used this interaction to complete a photoluminescence-excitation map of the Er3+ 4I13/2 manifold. This ability to interact directly with the states of an incarcerated ion suggests the possibility of coherently manipulating fullerene qubit states with light. © 2006 Elsevier B.V. All rights reserved.